Sanwei sandalwood decoction improves function of the gut microbiota in heart failure - Ma, Kuiying; Bai, Tingting; Hu, Pengfei; Zhao, Ming; Xiu, Zhi; Surilige; Dalintai; Zhang, Qingshan; Wan, Quan (Frontiers in Microbiology, 2023)
Objective: To investigate the effects of Sanwei sandalwood decoction on improving function of the intestinal flora in doxorubicin-induced heart failure in rats. Materials and methods: Thirty Sprague–Dawley rats were screened and randomly assigned into a blank group, a model group, and a Sanwei sandalwood decoction group (treatment group). The rat model of heart failure was prepared and established in the latter two groups. After successful model establishment, the treatment group received Sanwei sandalwood decoction by continuous gavage at 2g/kg, once daily for four weeks. The other groups were given an equivalent volume of saline. After the final dose, fecal samples were collected from each group and analyzed by macrogenomics and nontargeted metabolomics to characterize the intestinal flora and associated metabolites. Results: The composition of gut microbiota was significantly different between the three groups. There were 778,808 common genes between the blank and model groups, while 49,315 genes were lost and 521,008 were gained in the model group relative to the blank group. At the phylum level, all groups of rat fecal samples were dominated by Firmicutes, Bacteroidota, Actinobacteria, and Proteobacteria. At the genus level, the microbial community composition in all experimental groups of rat fecal samples was dominated by Lactobacillus, Bifidobacterium, Limosilactobacillus, Allobaculum, Prevotella, and Ligilactobacillus spp. Interestingly, cluster analysis was performed on the top 30 KEGG ontology (KO) terms displaying significant differences in relative abundance in the rat fecal microbiome among experimental groups. The relative frequency of posttranslational modification, coenzyme transport and metabolism, cell wall, membrane, and envelope biogenesis in the eggNOG and CAZy databases. In the nontargeted metabolomics, the group principal component analysis revealed that the groups were well distinguished from one another. The different metabolites were screened with VIP>1, and the KEGG different metabolite classification and enrichment analysis revealed that there includes 15 metabolites pathway, including loxoprofen, conifery-l-acetate, trichilin A, and others. The arachidonic acid pathway also accounted for a significant portion of the KEGG pathway classification analysis. Conclusions: Sanwei sandalwood decoction positively affects the intestinal microbial environment of rats with heart failure, improving the gut dysbiosis that is caused by the condition.